The Australo-Antarctic Columbia to Gondwana transition - Aitken,ARA; Betts,PG; Young,DA; Blankenship,DD; Roberts,JL; Siegert,MJ (Gondwana Research, 2016)
From the Mesoproterozoic to Cambrian, Australo-Antarctica was characterised by tectonic reconfiguration as part of the supercontinents Columbia, Rodinia and Gondwana. New tectonic knowledge of the Wilkes Land region of Antarctica allows Australo-Antarctic tectonic linkages to be resolved through reconstruction into ca. 160 Ma Gondwana. We also resolve 330 ± 30 km of sinistral strike-slip offset on the > 3000 km long Mundrabilla-Frost Shear Zone and 260 ± 20 km of dextral offset on the > 1000 km long Aurora Fault to reconstruct the ca. 1150 Ma geometry of Australo-Antarctica. Using this revised geometry, we derive the first model of the Columbia to Gondwana reconfiguration process that is geometrically constrained to ~ 100 km scale. In this model, early Mesoproterozoic tectonics is driven by two opposing subduction systems. A dominantly west-dipping subduction zone existed at the eastern margin of Australo-Antarctica until ca. 1.55–1.50 Ga. A predominantly east-dipping subduction zone operated at the western margin of the Mawson Craton from ca. 1.70 Ga to ca. 1.42 Ga. The latter caused gradual westwards motion and clockwise rotation of the Mawson Craton relative to the West and North Australian Craton and the accretion of a series of continental ribbons now preserved in the Musgrave Province and its southern extensions. A mid-Mesoproterozoic switch to predominantly west-dipping subduction beneath the West Australian Craton brought about the final closure of the Mawson Craton with the North and West Australian Craton along the Rodona-Totten Shear Zone. Convergence was achieved prior to 1.31 Ga, but final collision may not have occurred until ca. 1.29 Ga. Post-1.29 Ga intraplate activity involved prolonged high-temperature orogenesis from 1.22 to 1.12 Ga, and significant movement on the Mundrabilla-Frost Shear Zone between 1.13 and 1.09 Ga, perhaps in response to the assembly of Rodinia at ca. 1.1 Ga. The Australo-Antarctic Craton was amalgama